(untitled) (International relations and international law Journal, 2016)
In article globalization is considered as the stage of internationalization of economy connected to the changes in equipment, technology, the production organization when reproduction processes are leaving for national borders and the multinational companies and economic borders become organizing force leave for political and there are contradictions between internal and external factors of economic development that, in turn, make changes to national strategy of economic development.